PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KEARIFAN LOKAL SASAK UNTUK PENGUATAN PROFIL PELAJAR PANCASILA SISWA KELAS IV DI SD NEGERI 1 PENGENJEK - Nanda Sapriani; Khairun Nisa; Muhammad Sobri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to produce a valid and feasible Sasak Local Wisdom-Based LKPD for Strengthening the Pancasila Student Profile in Grade IV Civics Learning at SDN 1 Pengenjek. This research is a type of Research and Development (R&D). The data collection techniques used in this research are questionnaires and documentation. The results showed that the development of LKPD followed several ADDIE research processes, namely Analysis, Design, Development, Implementation, and Evaluation. The results of the validity and feasibility side show that the Sasak Local Wisdom-Based LKPD for Strengthening the Pancasila Profile of Grade IV Students at SDN 1 Pengenjek obtained a score with a percentage of 84% with very valid criteria from media experts, and a percentage of 92% with very valid criteria from material experts, a percentage of 80% with very feasible criteria from teacher responses, and a percentage of 83% with very feasible criteria from student responses. Based on the results of the data analysis obtained, the Sasak Local Wisdom-Based Learner Worksheet for Strengthening the Profile of Pancasila Students in Grade IV at SDN 1 Pengenjek is declared valid and feasible